The use of tracking tunnels to monitor the activity of small mammals in habitats associated with the northern wheatear (Oenanthe oenanthe) - Öberg, Meit (2009)
Nest predation is the main cause of nest mortality among birds and is thought to be the main reason for breeding failure amongst northern wheatears (Oenanthe oenanthe) in Swedish farmland habitats. Previous studies suggest that small mammalian predators and snakes are important nest predators for wheatears. However, other factors behind nest predation among wheatears have not been thoroughly studied. Here I used ink tracking tunnels (with a piece of meat as bait) to monitor the activity of small mammals in relation to landscape elements (such as linear, forest edge, open area, tall vegetation and stone piles) and land-use types (pastures, crop fields and ungrazed grasslands) in wheatear breeding territories.